Variability in soil redox response to seasonal flooding in a vernal pond - Barczok, Maximilian; Smith, Chelsea; Di Domenico, Nicolle; Kinsman-Costello, Lauren; Herndon, Elizabeth (Frontiers in Environmental Science, 2023)
Vernal ponds are ephemeral landscape features that experience intermittent flooding and drying, leading to variable saturation in underlying soils. Redox potential (Eh) is an important indicator of biogeochemical processes that changes in response to these hydrological shifts; however, high-resolution measurements of Eh in variably inundated environments remain sparse. In this study, the responses of soil Eh to ponding, drying, and rewetting of a vernal pond were investigated over a 5-month period from late spring through early autumn. Soil Eh was measured at 10-minute frequencies and at multiple soil depths (2 to 48 cm below the soil surface) in shallow and deep sections within the seasonally ponded lowland and in unsaturated soils of the surrounding upland. Over the study period, average Eh in surface soils (0-8cm) was oxidizing in the upland (753 ± 79 mV) but relatively reducing in the shallow lowland (369 ± 49 mV) and deep lowland (198 ± 37 mV). Reducing conditions (Eh < 300 mV) in surface soils prevailed for up to 6 days in the shallow lowland and up to 24 days in the deep lowland after surface water dried out. Intermittent reflooding resulted in multiple shifts between reducing and oxidizing conditions in the shallow lowland while the deep lowland remained reducing following reflooding. Soil Eh in the uplands was consistently oxidizing over the study period with transient increases in response to rain events. Reducing conditions in the lowland resulted in greater Fe-oxide dissolution and release of dissolved Fe and P into porewater than in the surrounding uplands. We determined that change in water depth alone was not a good indicator of soil Eh, and additional factors such as soil saturation and clay composition should be considered when predicting how Eh responds to surface flooding and drying. These findings highlight the spatial and temporal variability of Eh within ponds and have implications for how soil processes and ecosystem function are impacted by shifts in hydrology at terrestrial-aquatic interfaces.